THE ROLE OF AXIOLOGICAL APPROACHES IN THE FORMATION OF PATRIOTIC FEELINGS (American Journal of Interdisciplinary Research and Development, 2026)
In this article, attention is paid to the role of patriotism in the formation of national mind and social values. It is important in strengthening patriotism, national identity, and its senses and forms the attitude of the population to a historical and cultural heritage. An article in the article is an analysis of the expression of patriotism in the educational, cultural and media.